tmRNA-mediated trans-translation as the major ribosome rescue system in a bacterial cell - Himeno, Hyouta; Kurita, Daisuke; Muto, Akira (Frontiers in Genetics, 2014)
Transfer messenger RNA (tmRNA; also known as 10Sa RNA or SsrA RNA) is a small RNA molecule that is conserved among bacteria. It has structural and functional similarities to tRNA: it has an upper half of the tRNA-like structure, its 5’ end is processed by RNase P, it has typical tRNA-specific base modifications, it is aminoacylated with alanine, it binds to EF-Tu after aminoacylation and it enters the ribosome with EF-Tu and GTP. However, tmRNA lacks an anticodon, and instead it has a coding sequence for a short peptide called tag-peptide. An elaborate interplay of actions of tmRNA as both tRNA and mRNA with the help of a tmRNA-binding protein, SmpB, facilitates trans-translation, which produces a single polypeptide from two mRNA molecules. Initially alanyl-tmRNA in complex with EF-Tu and SmpB enters the vacant A-site of the stalled ribosome like aminoacyl-tRNA but without a codon–anticodon interaction, and subsequently truncated mRNA is replaced with the tag-encoding region of tmRNA. During these processes, not only tmRNA but also SmpB structurally and functionally mimics both tRNA and mRNA. Thus trans-translation rescues the stalled ribosome, thereby allowing recycling of the ribosome. Since the tag-peptide serves as a target of AAA+ proteases, the trans-translation products are preferentially degraded so that they do not accumulate in the cell. Although alternative rescue systems have recently been revealed, trans-translation is the only system that universally exists in bacteria. Furthermore, it is unique in that it employs a small RNA and that it prevents accumulation of non-functional proteins from truncated mRNA in the cell. It might play the major role in rescuing the stalled translation in the bacterial cell.